Laboratory confirmation of meningococcal disease in Scotland, 1993–9. Issue 1 (1st January 2002) - Clarke, S C; Reid, J; Thom, L; Denham, B C; Edwards, G F S
Abstract : Aims: To describe the laboratory confirmation of meningococcal disease, using culture and non-culture based techniques, between 1993 and 1999 as part of a national service in Scotland. Methods: Samples from patients with suspected meningococcal disease in Scotland were analysed by culture and non-culture based techniques to gain a laboratory confirmation of disease. Data were analysed to establish the number of disease cases, the serogroups of the organisms involved, and the importance of the techniques used. Results: Between 1993 and 1999, there was a total of 1749 notified cases of meningococcal disease in Scotland. Culture based methods provided a laboratory confirmation of 788 cases whereas non-culture techniques confirmed 461 cases. Conclusions: Non-culture techniques were a useful addition to culture based techniques in Scotland and improved the dataset required for public health management, disease surveillance, and vaccine policy.